Mount Tabor in the Metropolitan Platon’ Bethany (Vifaniia) Monastery: Typology, Function, Iconography - Bashkirova, Mariya A. (Actual Problems of Theory and History of Art, 2023)
The article examines the so-called Tabor, which was built in 1783–1785 by order of Metropolitan Platon (Levshin) for the cathedral of the Bethany Monastery. Being considered in a “coordinate system” that includes type, function and iconography, Tabor has been presented as a completely original work, carried out, however, in close connection with modern European architecture. This structure was an imitation of a rock covered with artificial plants, crowned with a rotunda-altar, and typologically belonged to the number of park grottoes. According to the descriptions during Plato’s lifetime and up to the middle of the 19th century, there were naturalistic images of river streams and animals on the slopes. The lower Lazarevsky “chapel” was located inside this structure, imitating a crypt, and subsequently the tomb of Metropolitan Plato was arranged here. During the divine service, the Bethany Tabor was also used as an ambo. The interior of the cathedral reads the iconographic scheme of the Church of the Holy Sepulchre, but the idea of reproducing sacred mountain landscapes dates back to the art of the Baroque.Thus, the prototype of Metropolitan Plato’s plan was most likely the tabernacle in the form of Mount Sinai, commissioned by Prince Grigory Potemkin for the Assumption Cathedral of the Moscow Kremlin. The forms of the Bethany Cathedral with the Tabor testify to the high skill of a project creator, regardless somewhat awkward embodiment and later reconstructions. They find close parallels in the architecture of the French neoclassicists of the 1780s, reminiscent of the Northern Italian Sacri Monti of the 17th century — the idea to enclose an imitation of a rock inside an architectural structure.
Keywords: The Bethany Monastery; Vifaniia Monastery; Metropolitian Platon Levshin; Grigory Potemkin; festival architecture; sacred topography; grotto; French neoclassicism; Church of the Holy Sepulchre; Sacri Monti